Kajian Alih Wahana Cerita “Kedai Kopi Odyssey” Karya Leopold A. Surya Indrawan menjadi Naskah Drama - Een Nurhasanah (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2022)
The research study on the transfer of the story “Kedai Kopi Odyssey” by Leopold A. Surya Indrawan in the short story collection “Particles of God” Kompas 2014 aims to examine the process of converting stories into drama scripts and also analyze the social values contained therein. The selection of stories is based on the content of stories that contain social conflict. It is related to the approach used by the researcher, namely the sociology of literature approach. In addition to the sociology of literature approach, the researcher examines the process of transferring the story of “Kedai Kopi Odyssey” into a drama script. The analysis process is based on the intrinsic and extrinsic elements of literary works, then on transferring stories into drama scripts. Based on the analysis results, social values such as the value of tolerance and changes in sentence and diction in translating stories into drama scripts.